2018
DOI: 10.1007/s13595-018-0708-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of Quercus robur L. to taproot pruning: a 5-year case study

Abstract: & Key message Quercus robur seedling mass was affected more by planting density than by taproot pruning. Root pruning enhanced stem biomass at the expense of roots in later growth stages. Alteration of biomass allocation due to nursery practices may result in greater susceptibility to injury and death of the seedlings under unfavorable environmental conditions. & Context Plants adjust their growth and modulate the resource allocation in response to applied treatments and environmental conditions. & Aims The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…In the present study, radicle pruning significantly increased the root-toshoot ratio and the number of taproots irrespective of oak species. These results are different from the study by Zhang et al (2016) that radicle pruning by acorn-eating animals shows no effect on seedling performance of Q. variabilis seedlings, but are in agreement with Mucha et al (2018) showing that root-pruning generates lower root mass and higher stem mass of seedlings. This difference can be largely attributed to the length at which the radicle is pruned or to the oak species investigated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, radicle pruning significantly increased the root-toshoot ratio and the number of taproots irrespective of oak species. These results are different from the study by Zhang et al (2016) that radicle pruning by acorn-eating animals shows no effect on seedling performance of Q. variabilis seedlings, but are in agreement with Mucha et al (2018) showing that root-pruning generates lower root mass and higher stem mass of seedlings. This difference can be largely attributed to the length at which the radicle is pruned or to the oak species investigated.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, radicle pruning by T. sibiricus increased shoot mass and substantially reduced the root-to-shoot mass ratio especially in 2 temperate oak species, Q. variabilis and Q. aliena, reflecting a reduction in the size of taproot favoring a more branched root system. The branched multiple taproots are expected to promote seedling development because root surface area will be larger than that of seedlings with a single taproot (Devine et al 2009;Rodríguez et al 2015). Therefore, it can be anticipated that seedlings producing a more branched root system due to radicle pruning by seed-eating animals might be more successful in the field (Schultz & Thompson 1990;Liu et al 2016;Van Sambeek et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results of type 3 test of fixed effects from the MIXED Procedure demonstrated no significant effect on trunk size from the way the seedlings were handled during transplant (we also considered growth instead of trunk size, but the conclusions regarding statistical significance were unchanged). Wood (1996) with 3-year-old pecan transplants, Zhang et al (2015) with newly sprouted pecan seedlings, and Mucha et al (2018) with english oak (Quercus robur) trees also found little effect of taproot pruning on tree growth.…”
Section: Resultsmentioning
confidence: 99%
“…This redirection of biomass may contribute to the plant's ability to escape or overcome the pathogen invasion. It may also be simply a consequence of oak's ontogenetic development; Mucha et al (2018) found that enhanced allocation of biomass to the stem was detectable 5 years after root pruning in a soil environment free from root pathogens. Andersen, Rasmussen, and Brander (2000), however, reported that both root and shoot biomass were reduced in oaks in response to root trimming.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of taproot pruning at a depth of 10-15 cm modifies the natural development of the oak root system, especially since this procedure may be repeated more than once depending on the production cycle, such as after the 1st and 2nd year of production. It is known that oak seedlings with damaged, severed or pruned taproots do not regenerate them (Mucha et al, 2018;Ogievskii & Popova, 1954;Zadworny, Jagodziński, Łakomy, Ufnalski, & Oleksyn2014), and therefore have reduced ability to access deeper sources of water. The lack of a taproot thus contributes to reduced survival of oaks in response to episodes of long-term drought.…”
Section: Introductionmentioning
confidence: 99%